The Effect of Additive ZRJ-S1 on Mechanical Properties of Portland Cement - Xin Zeng; Ping Zhou; Jichang Tong; Hao Wang; Lin Zhao; Weidong Meng; Ming Li (Advances in Materials Science and Engineering)
For mechanical performance perfection of cement-based material, toughening materials are often added to the cement system, such as solid particles, carbon-based material, or other inorganic/organic materials. Compared with other materials, carbon-based materials have better compatibility and are more likely to form a cross-linked network structure in the cement system, which can significantly improve the mechanical properties of cement stone. In this review, a new type carbon-based material ZRJ-S1 was used as a mechanical additive to reinforce oil well cement. In this experiment, ZRJ-S1 was explored with microlevel scale and showed the thin-layer sheet morphology. With static mechanical-strength test, ZRJ-S1 reinforced cement-based material was found with excellent mechanical improvement when 0.05 wt% ZRJ-S1 additive was used, that is, compressive strength improved to 150.9% of that of control sample, splitting tensile strength improved to 134%, and flexural strength improved to 129.2%. Furthermore, the weight percentage superiority of ZRJ-S1 was researched by dynamic stress-train mechanical test and found the mechanical elasticity improvement in which Poisson ratio improved by 74% and formed elasticity modulus reduced to 65.4% when resisting to mechanical damage. The effect of ZRJ-S1 on the microstructure of cement-based materials was studied. As a result, ZRJ-S1 was found with the bridging effect for completion of cement-based material, crack deflection effect for controlling microcrack propagation, and pulling-out effect for preventing immediate fracture of cement-based material itself. Then, using about 0.05% of ZRJ-S1 achieved the accelerating effect on hydration, the speed of the cement-based material, in which more C-S-H gel was formed. Moreover, adding of microscale ZRJ-S1 showed denser spatial microstructure and excellent control ability to pore structure of cement-based material. Micropore percentage of more than 200 nm size, which was with serious damage to mechanical performance, was decreased from 17.40 to 11.89%, and porosity of cement-based material itself decreased to 16.20%. As a result, ZRJ-S1 additive showed excellent reinforcement effect on Portland cement.